Desipramine targets astrocytes to attenuate synaptic plasticity via modulation of the ephrinA3/EphA4 signalling. (June 2016) - Tanasic, Sascha; Mattusch, Corinna; Wagner, Eva Maria; Eder, Matthias; Rupprecht, Rainer; Rammes, Gerhard; Di Benedetto, Barbara
Abstract: Long-term potentiation (LTP), a major cellular correlate of memory storage, depends on activation of the ERK/MAPK signalling pathway, but the cell type-specific localization of activated MAPKs remains unknown. We found that in the CA1 field of the hippocampus, shortly after LTP induction, an increase in the number of MAPK-positive cells occurred specifically among astrocytes of the stratum radiatum, suggesting a putative role of astrocytes for LTP. Desipramine (DMI) is an antidepressant which is used to treat major depressive disorder, but also other pathologies such as neuropathic pain or attention-deficit/hyperactivity disorder. Tricyclic antidepressants such as DMI may cause memory impairment as a side effect. However, biological underpinnings of this effect still remain unclear. Here, we show that DMI inhibited the astrocytic MAPK activation and thereby hindered synaptic potentiation. These effects correlated with a reduced neuronal activation in the stratum pyramidale, thereby prompting us to analyse a regulator of LTP located at the astrocyte-neuron interface in the stratum radiatum, namely the ephrinA3/EphA4 signalling pathway. DMI enhanced EphA4 clustering, which favoured an increased ephrinA3-mediated EphA4 phosphorylation and elevated EphA4 forward signalling. The co-administration of DMI with the Src inhibitor SU6656, which blocks EphA4 forward signalling, could partially reverse the LTP attenuation, further supporting the targeting of the ephrinA3/EphA4 pathway by DMI. Thus, our findings suggest a putative novel mechanism for DMI to modulate LTP through the regulation of the ephrinA3/EphA4 signalling pathway. A further exploration of the molecular and behavioral consequences of targeting ephrinA3/EphA4 might help to improve the clinical use of DMI. Highlights: Induction of LTP in hippocampus activates ERK/MAPK in astrocytes. LTP and the ERK/MAPK peak in astrocytes are inhibited by desipramine. The glia-neuron ephrinA3/EphA4 signalling pathway is targeted by desipramine. EphA4 activity is increased by desipramine and might affect LTP. Blockade of EphA4 overactivation by SU5565 partially rescues LTP.